DAMPAK SISTEM ZONASI PENERIMAAN PESERTA DIDIK TERHADAP EFEKTIVITAS PEMBELAJARAN - Lailatul Khudoifah; Ainul Yaqin; Hajar Nurma Wachidah (At- Ta'lim : Jurnal Pendidikan, 2023)
The impact of the student acceptance zoning system on learning effectiveness is motivated by the Indonesian government's policy target for the Ministry of Education and Culture, namely equal distribution of quality education. At least it is prioritized for the younger generation (students) to get the same quality of education. It is impossible to adjust the teacher's teaching ability in a short time. As a result, the teaching and learning process in the classroom cannot be carried out properly. In addition to the problems faced by teachers, students also face challenges because of the diverse class composition. This study aims to analyze the zoning system, determine and analyze the level of effectiveness of learning, analyze the impact of the zoning system on learning effectiveness. The method used is a quantitative descriptive method with a correlation approach, the correlation in question is to determine the relationship between two variables, namely the impact of the student acceptance zoning system (variable X) and Learning Effectiveness (variable Y). In this method, researchers only see something by distributing questionnaires without doing or changing anything. The population in this study amounted to 1041 students with a sample of 10%, namely 91 students with random sampling data. The results of this study were obtained from the results of the correlation data analysis. There was no effect, namely obtaining a significant value of 0.320 > 0.05 or Pearson correlation -0.106 < rtable 0.204. This shows that there is no impact between the Student Acceptance Zoning System on Learning Effectiveness. Thus it can be concluded that Ha is rejected and Ho is accepted.